The 100 Brasilia Rules and access to justice in Brazil - Gonet Branco, Paulo Gustavo (2020)
This paper addresses the problem of access to justice in recent centuries, its historical evolution and the repercussions of the approval of the Brasilia Rules and their implementation in countries of the IberoAmerican region, in particular, in the justice system of Brazil. Thus, the energetic institutional strategy implemented by the Brazilian State to improve the resolution of conflicts for the benefit of the rights and interests of the most vulnerable will be analysed.